Anatomical description of the brain wax models of Museu da Pharmacia de Ouro Preto - Sousa, Luiz Eduardo; Borges, Ingrid da Silva; Seidel, Helen; Pereira, Isadora Lopes; Farias, Juliana de Paula (Arquivos de Neuro-Psiquiatria, 2022)
Background In 1839, the Escola de Farmácia de Ouro Preto pioneered the teaching of pharmaceutical sciences in Brazil. At the end of the 19th century, the Escola de Farmácia possessed a French collection of anatomical models, some made of wax and paper-mâché. The models were a critical part of teaching anatomy, particularly in an era of paradigm changes about how the human brain works.Objective The present study aimed to anatomically describe the brain models through a comparative analysis with the current anatomical description.Methods Comparative analysis of the brain models with modern anatomical descriptions.Results In the individual analysis of the wax models, we verified excellent anatomical accuracy of the cortical and subcortical regions. Our results identified internal structures, like the basal ganglia and white matter. Compared with modern anatomical books and websites, the wax brain models have high scientific quality.Conclusion The models of the present study gave students hands-on experience of human anatomy in the 19th century. Nowadays, the models are part of the memory of Universidade Federal de Ouro Preto and Museu da Pharmacia de Ouro Preto . The collection of wax models shows the appreciation of neuroanatomy teaching at the turn of the century concomitant with advances in neurology and anatomy around the world.
Keywords: Models; Anatomic; Neuroanatomy; Education; History